KOREAN WAVE: PHILOSOPHY, EXISTENCE, PHENOMENON, AND RESPONSE OF YOUNG MUSLIM - Pramana, M. Agung; Masduki, Masduki (UIN Antasari Banjarmasin, 2024)
This article analyzes the Korean wave, which is intensively entering the transnational market. Focusing on Korean dramas, which are mushrooming in Indonesia, previous studies only focused on the development of the Korean wave in the world. They only took into account the values contained therein. More than that, this research comes as a novelty with a discussion of young Indonesian Muslims who consume Korean dramas as active consumers. This research collaborates with young Muslims, most of whom consist of students, especially in Riau province, regarding the meaning of Korean dramas in Indonesia. This article attempts to answer the main questions, such as how young Muslims in Riau respond to interpreting the Korean dramas shown. Meanwhile, further questions, such as how the journey and development of Korean dramas are in the Indonesian context, are also asked. The author used a qualitative method to answer this question based on online interviews with 24 young Indonesian Muslims via a Google form link. Then, it will be analyzed using relevant previous literature. The research results show that young Muslims consume Korean dramas not only as passive recipients. Do not just watch it. More than that, they are also active consumers who are critical in learning, teaching new insights, and learning the Korean language and the good values contained therein. They appear as active consumers who can take lessons and even teach from the Korean dramas they watch.